FRI0318 THROMBOCYTOPENIA AND MULTI-ORGAN INVOLVEMENT MIGHT BE POOR PROGNOSTIC FACTORS FOR SYSTEMIC SCLEROSIS CARDIOMYOPATHY. (June 2019) - Wei, Xiuning; Yang, Lijuan; Zheng, Donghui; Dai, Lie
Abstract : Background: Systemic Sclerosis (SSc)-cardiomyopathy is associated with a high mortality in SSc. It is important to identify potential prognostic factors for SSc-cardiomyopathy. Objectives: To describe the clinical characteristics and identify potential prognostic factors for patients with SSc-cardiomyopathy. Methods: We retrospectively reviewed the clinical data of SSc-cardiomyopathy patients hospitalized at Sun Yat-Sen Memorial Hospital from January 1992 to November 2018. SSc-cardiomyopathy was defined as structurally and functionally abnormal of heart muscle in SSc patients with cardiac symptoms. Coronary artery disease, hypertension, valvular disease and congenital heart disease were excluded.The Chi-square test was used to compare the differences between the death group and the survival group. Results: There were 903 SSc patients recruited and 20 patients (2.2%) of them were SSc–cardiomyopathy. Among these 20 patients, 65% were females, age was 52.8±13.2 years, disease duration was 3.1±2.3 years, duration from SSc onset to cardiomyopathy occurred was 2.8±2.3 years. SSc–cardiomyopathy developed in 18 patients (90%) with diffuse cutaneous SSc (dcSSc), and in 2 patients (10%) with limited cutaneous SSc (lcSSc). Eleven patients (55%) had pulmonary fibrosis, 7 patients (35%) had pulmonary arterial hypertension (PAH), 5 patients (25%) had scleroderma renal crisis (SRC) and esophageal involved respectively, 6 patients (30%) manifested thrombocytopenia and 4 patients (20%) manifested anemia. Cardiac symptoms included shortness of breath (n=18), palpitation (n=6), edema of lower extremity (n=4), fatigue (n=5) and/or cough (n=3). All patients were found to have cardiomegaly by echocardiography (UCG) or chest radiography. Left ventricular ejection fraction (47±15%) were decreased. Ventricular wall motion abnormality was found in 5 patients (25%) by UCG. 15 patients (75%) manifested cardiac arrythmia in electrocardiogram, with frequent premature ventricular contractions were the most common (n=10, 50%). Myocardial injury was found in 14 patients (70%) by electrocardiogram. Myocarditis was found in 7 patients (35%) by myocardial enzyme assay. Nine patients (45%) died, the causes of death were heart failure (n=4, 45%), sudden death (n=3, 33%) and ventricular tachycardia (n=2, 22%). 5 patients (55.6%) died within 1 month after the onset of cardiac symptoms. 3 patients died within 2 month, and one patient with implantable cardioversion defibrillation (ICD) died 2 years after ICD implanted. Ten patients survived in a mean 6 (1∼10) years follow–up. Six patients (67%) manifested thrombocytopenia and 4 patients (44%) manifested anemia in the death group. However, only one patient (9.1%) in survival group manifested thrombocytopenia (p=0.007) and anemia (p=0.069). There were more organs and systems involved in the death group, compared to the survival group (4±2 vs 2±1, p=0.044). 4 patients had SRC in death group, while 2 patients had SRC in survival group. 6 patients had pulmonary fibrosis in death group, while 5 patients in survival group (Table 1 ). Conclusion: Thrombocytopenia and multi-organ involvement might be poor prognostic factors for patients of SSc-cardiomyopathy. Disclosure of Interests: None declared